2014
DOI: 10.1371/journal.pone.0109562
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Phase-Contrast Tomography of Renal Ischemia-Reperfusion Damage

Abstract: PurposeThe aim of the study was to investigate microstructural changes occurring in unilateral renal ischemia-reperfusion injury in a murine animal model using synchrotron radiation.Material and MethodsThe effects of renal ischemia-reperfusion were investigated in a murine animal model of unilateral ischemia. Kidney samples were harvested on day 18. Grating-Based Phase-Contrast Imaging (GB-PCI) of the paraffin-embedded kidney samples was performed at a Synchrotron Radiation Facility (beam energy of 19 keV). To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 58 publications
2
18
0
2
Order By: Relevance
“…4 ), with the additional benefit of providing non-distorted and fast 3D information. The staining method presented here yielded micro-CT images of a mouse kidney and a mouse cerebellum at a level of detail that is only available from other multiple sectioning techniques or highly sophisticated large-scale-facility-based X-ray methods 26 27 . Probably the biggest advantage over other lab-based techniques is the relatively fast (few hours) data acquisition, and the non-destructive and non-distorted 3D imaging visualisation.…”
Section: Discussionmentioning
confidence: 99%
“…4 ), with the additional benefit of providing non-distorted and fast 3D information. The staining method presented here yielded micro-CT images of a mouse kidney and a mouse cerebellum at a level of detail that is only available from other multiple sectioning techniques or highly sophisticated large-scale-facility-based X-ray methods 26 27 . Probably the biggest advantage over other lab-based techniques is the relatively fast (few hours) data acquisition, and the non-destructive and non-distorted 3D imaging visualisation.…”
Section: Discussionmentioning
confidence: 99%
“…Differently from the conventional (attenuation-based) microCT in which the contrast is due to attenuation differences within the sample, in PhC-microCT the contrast originates from the phase shift of the X-ray beam passing through the matter (Snigirev et al, 1995 ; Bravin et al, 2013 ). This phase shift in non-mineralized biological tissues can be up to three orders of magnitude larger than attenuation (Momose et al, 1996 ; Lewis et al, 2003 ), explaining the highly increased contrast that has been observed with PhC-microCT imaging in investigating esophagus (Lewis et al, 2003 ), brain (Connor et al, 2009 ; Pinzer et al, 2012 ; Marinescu et al, 2013 ), liver (Lewis et al, 2003 ; Herzen et al, 2014 ), kidney (Velroyen et al, 2014 ), lung (Lewis et al, 2003 ), cartilage (Coan et al, 2010 ; Marenzana et al, 2012 ; Horng et al, 2014 ) and breast tissues (Arfelli et al, 2000 ; Stampanoni et al, 2011 ).…”
Section: Approaching Synchrotron Phase Tomography Methodsmentioning
confidence: 99%
“…[12][13][14] Particularly in the imaging blood vessels, microvascular architectures in various organs (such as liver, heart and kidney) have been clearly presented via PCCT without contrast agents at micrometer or even submicrometer level. [15][16][17] High-resolution 3D visualization of the microvascular networks obtained by PCCT provides new possibilities for analyzing and characterizing 3D anatomical features of the vessels, especially for differentiating between healthy and diseased vessels. 18,19 Currently, most studies focused on demonstrating the high significance of the PCCT in analysis of brain vascular networks in small animals.…”
Section: Introductionmentioning
confidence: 99%